KARAKTERISTIK IBU BERHUBUNGAN DENGAN PERSEPSI IBU TERHADAP BUKU KESEHATAN IBU DAN ANAK (KIA) - Vianty Mutya Sari; Nurhasanah Nurhasanah (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
Background: In Indonesia, breast cancer is the second leading cause of death for women after cervical cancer. Based on data from the Cirebon City Health Office in 2015, the number of maternal deaths was 4/5400 live births, the number of infant deaths was 25/5455 live births, the number of under-five deaths was 8/5378 live births. The aspects of maternal and child health can be seen from several indicators of achievement, one of which is Infant Immunization, in 2015 out of 22 urban villages in the city of Cirebon there was only one sub-district that had not reached the target, namely in the Argasunya sub-district. While the coverage of health care delivery in Argasunya was 52.64% (from data on the coverage of health care workers, 108.37%, only 55.73% gave birth at the health facility) and the highest birth attendance by traditional birth attendants in Cirebon was in the Argasunya village of 4.63%.The purpose of this study was to determine the relationship between characteristics and perceptions of pregnant women on the MCH HandbookMethods: This study used a cross sectional design. The population of all pregnant women in Benda Kerep Village, Argasunya Village, Cirebon City. Sampling using total sampling. The data taken is primary data obtained through a questionnaire given to 23 pregnant women. Correlation test used is Chi-Square.Research Results The majority of pregnant women had a poor perception of the MCH handbook (69.56%). The majority of pregnant women have an age of 20-35 (87%). The majority of education for pregnant women (completing SD) (78%). The majority of gestational age is included in the second trimester, namely 14-27 weeks (48%). The majority of pregnant women had a planned place of delivery at home (73.92%). Conclusion Based on occupation, all pregnant women are not working (100%). There is no relationship between the age of pregnant women and the mother's perception of the MCH handbook. There is no relationship between the education of pregnant women and the mother's perception of the MCH handbook. There is no relationship between the occupation of pregnant women and the mother's perception of the MCH handbook. There is no relationship between the planning of the place of delivery of pregnant women and the perceptions of mothers towards the MCH handbook.Suggestions Future research is expected to be able to examine it more deeply by adding other components currently contained in the latest edition of the MCH book using the appropriate method. Keywords: Characteristics, Perception, MCH Handbook ABSTRAK Latar Belakang : Di Indonesia, Kanker payudara menduduki peringkat kedua penyebab kematian wanita setelah kanker leher rahm. Berdasarkan data Dinas Kesehatan Kota Cirebon Tahun 2015, jumlah kematian Ibu 4/5400 kelahiran hidup, jumlah kematian bayi 25/5455 kelahiran hidup, jumlah kematian balita 8/5378 kelahiran hidup. Aspek kesehatan ibu dan anak dapat di lihat dari beberapa indikator pencapaian salahsatunya Imunisasi Bayi, pada tahun 2015 dari 22 kelurahan di kota Cirebon hanya ada satu kelurahan yang belum mencapai target yaitu di kelurahan Argasunya. Sedangkan cakupan persalinan naskes di Argasunya sebesar 52,64% (dari data cakupan persalinan nakes 108,37% hanya 55,73% yang bersalin di Faskes) dan pertolongan persalinan oleh dukun tertinggi di kota cirebon adalah di kelurahan argasunya sebesar 4,63%.Tujuan dari penelitian ini adalah untuk mengetahui hubungan Karakteristik dengan persepsi Ibu hamil terhadap Buku KIAMetode : Penelitian ini menggunakan desain cross sectional. Populasi seluruh ibu hamil di Desa Benda Kerep Kelurahan Argasunya Kota Cirebon. Pengambilan sampel dengan menggunakan Total sampling. Data yang diambil merupakan data primer yang didapat melalui wawancara kepada 23 ibu hamil dengan menggunakan kuesioner. Uji Korelasi yang digunakan adalah Chi-Square.Hasil :Mayoritas ibu hamil memiliki persepsi yang kurang baik terhadap buku KIA (69,56 %). Mayoritas Ibu hamil memiliki usia 20-35 (87%). Mayoritas pendidikan ibu hamil (Tamat SD) (78%). Mayoritas Usia kehamilan adalah termasuk trimester II yaitu 14-27 minggu (48%). Mayoritas ibu hamil memiliki rencana tempat persalinan adalah di rumah (73,92%).Kesimpulan Berdasarkan pekerjaan seluruh ibu hamil tidak bekerja (100%). Tidak ada hubungan antara usia ibu hamil dengan persepsi ibu terhdapa buku KIA. Tidak ada hubungan antara pendidikan ibu hamil dengan persepsi ibu terhdapa buku KIA. Tidak ada hubungan antara pekerjaan ibu hamil dengan persepsi ibu terhdapa buku KIA. Tidak ada hubungan antara rencana tempat bersalin ibu hamil dengan persepsi ibu terhadap buku KIA.Saran Penelitian selanjutnya diharapkan dapat mengkaji lebih dalam dengan menambahkan komponen-komponen lain yang saat ini terdapat pada buku KIA edisi terbaru menggunakan metode yang sesuai. Kata Kunci : Karakteristik, Persepsi, Buku KIA